2019
DOI: 10.1002/adhm.201901228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fiber Stiffness on Meniscal Cell Migration into Dense Fibrous Networks

Abstract: Fibrous scaffolds fabricated via electrospinning are being explored to repair injuries within dense connective tissues. However, there is still much to be understood regarding the appropriate scaffold properties that best support tissue repair. In this study, the influence of the stiffness of electrospun fibers on cell invasion into fibrous scaffolds is investigated. Specifically, soft and stiff electrospun fibrous networks are fabricated from crosslinked methacrylated hyaluronic acid (MeHA), where the stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…22,30 One of the important criteria required for meniscal regeneration is that the injected biomaterials should provide a suitable mechanical function. A recent study by Song et al 47 showed that the hydrogel with a stiff mechanical property allowed faster fibrochondrocyte migration to fill the meniscal tissue defect as compared with soft hydrogel. In this study, we simply introduced PEO, which has a high molecular weight polyethylene glycol (PEG; 100,000 g/mol) and is an FDA-approved biomaterial and which was selected because it can attract water molecules within the network structure for increased mechanical stability.…”
Section: Discussionmentioning
confidence: 99%
“…22,30 One of the important criteria required for meniscal regeneration is that the injected biomaterials should provide a suitable mechanical function. A recent study by Song et al 47 showed that the hydrogel with a stiff mechanical property allowed faster fibrochondrocyte migration to fill the meniscal tissue defect as compared with soft hydrogel. In this study, we simply introduced PEO, which has a high molecular weight polyethylene glycol (PEG; 100,000 g/mol) and is an FDA-approved biomaterial and which was selected because it can attract water molecules within the network structure for increased mechanical stability.…”
Section: Discussionmentioning
confidence: 99%
“…Current dynamic endothelial models applied the cells on a 2D flat surface-either a wall of a microchannel, the bottom of a reservoir, or a sealed porous membrane. However, some recent studies have shown that the biophysical cues of an ECM can affect cellular activities 13,[29][30][31] . Therefore, we hypothesized that the aligned fibrous topography (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, stiffness and degradability do not only direct cell differentiation 54,55 , but also may influence invasion 32 . Biochemical cues such as receptor-binding peptides and CMPs have been shown to modulate cell bioactivity 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Engineered hydrogels, such as functionalized poly(ethylene glycol) (PEG) hydrogels, are designed for delivery of targeted cellular instructions via tunable control of mechanical and biochemical environments [23][24][25][26] . Such cell-instructive hydrogels and scaffolds are attractive alternatives to cell-based tendon therapies because these materials do not rely on allogenic cell use and therefore reduce cell-donor site morbidity and immune rejection [27][28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%